Assessment of the Influence of Natural Conditions on the Accumulation of Human Capital in the Eastern Regions of the Russian Empire in the Late 19th — Early 20th Century - D. V. Didenko; E. S. Grishin (Историко-географический журнал)
The article presents a methodology for quantitative analysis of the influence of the natural-geographical environment on the accumulation of human capital and its testing on the data from the Asian part of the Russian Empire in the late 19th — early 20th centuries. The territorial unit of analysis is an uezd or district as a set of urban and rural settlements, an internal part of larger administrative entities, namely provinces and regions. The regression analysis showed that geographical factors are statistically significantly associated with the formation of human capital in the territory of the Eastern part of late imperial Russia. The research work was carried out based on a wide range of statistical and cartographic sources, including data from the 1897 census, reference maps of the 1914 atlas, climatic atlases of the Russian Empire and others. The significance and quantitative estimates of various factors (climate, natural resources, share of the urban population, and others) of human capital accumulation depending on the sample are presented. The article shows in detail the progress of the work and its methodology, including the identification of significant factors of literacy disparity in the context of “urban/rural” and “male/female” population». Input data and results of regression analysis are provided in the corresponding tables. The processed data set was presented as a composition of cartographic materials. Thus, topical maps were prepared for the source data, in particular on natural resources and climate; statistical results on disparity were displayed in the form of cartograms.